Makna Kesinambungan Kampanye Green Beauty oleh Kosmetik Garnier - Neldy Maria Lesilolo; Rustono Farady Marta; Rewindinar Rewindinar (Koneksi, 2021)
The Garnier green beauty campaign conveys a message to the public through advertising media. The message is conveyed to the public regarding environmental activities that have a sustainable meaning. The green beauty campaign through advertising media shows Garnier's environmental friendly actions. Cause consumer behavior that turns into a form of responsible attitude. The purpose of this study was to determine the meaning of the sustainability of the green beauty campaign through Garnier's cosmetic advertising media. Researchers used a qualitative approach with Ferdinand de Saussure's semiotic analysis method which was signifier and signified. Methods of data collection with the method of documentation. The object of research was through the green beauty campaign advertisement and the subject of Garnier. The one-minute green beauty campaign ad is divided into seven scenes. The results of this study found the meaning of sustainability, by taking real action to become green beauty. Being green beauty is explained through verbal and non-verbal signs. Marked by each scene of the Garnier green beauty campaign advertisement, the meaning of sustainability is found. The real action starts from the production process to processing Garnier cosmetic waste.Kampanye Garnier green beauty menyampaikan pesan kepada masyarakat melalui media iklan. Pesan yang disampaikan kepada khalayak mengenai kegiatan peduli lingkungan yang memiliki makna berkesinambungan. Kampanye green beauty melalui media iklan menunjukan aksi nyata Garnier yang ramah lingkungan. Menyebabkan perilaku konsumen yang berubah menjadi wujud sikap yang bertanggung jawab. Tujuan penelitian ini untuk mengetahui makna kesinambungan dari kampanye green beauty melalui media iklan kosmetik Garnier. Peneliti menggunakan pendekatan kualitatif dengan metode analisis semiotika Ferdinand de Saussure secara signifier dan signified. Metode pengumpulan data dengan metode dokumentasi. Objek penelitian melalui iklan kampanye green beauty dan subjek Garnier. Iklan kampanye green beauty yang berdurasi satu menit dibagi menjadi tujuh scene. Hasil Penelitian ini menemukan makna kesinambungan, dengan melakukan aksi nyata menjadi green beauty. Menjadi green beauty dijelaskan melalui tanda secara verbal dan non verbal. Ditandai melalui setiap scene iklan kampanye Garnier green beauty memiliki makna kesinambungan yang ditemukan. Aksi nyata dimulai dari proses produksi sampai pengolahan limbah kosmetik Garnier.